Effects of fluid bed agglomeration on the structure modification and reconstitution behaviour of milk protein isolate powders. (December 2015) - Ji, Junfu; Cronin, Kevin; Fitzpatrick, John; Fenelon, Mark; Miao, Song
Highlights: Agglomeration of MPI powders decreases the bulk density and increases the porosity. Using water as a binder in agglomeration forms the most irregular shaped particles. Using lactose as a binder in MPI agglomeration gives the best wettability. None of the binders plays a beneficial role on solubilisation of MPI agglomerates. Large agglomerates showed better wettability but no improvement for solubilisation. Abstract: The effects of agglomeration on the density, morphology and subsequent reconstitution behaviours of milk powders were investigated. In this study, milk protein isolate, as a model system, was agglomerated in a fluid bed granulator with three different binders: water, lactose and sucrose solution ( 15% w/v ). Morphology was quantified by circularity, convexity and elongation. Wettability was measured by the modified Washburn method. Powders solubilisation was quantified by dynamic particle size measurement and the kinetics of dissolved solids concentration in solution. The results showed that granules with water as the binder produced significantly lowest circularity and convexity and highest elongation. An increase in the size of the agglomerated MPI corresponded with an increase in the wettability but a decrease in the ability of solubilisation in water. Granules agglomerated with hydrophilic sugars were found to contribute differently which improved the wettability significantly but no improvement for the kinetics of dissolution.